Vaccine hesitancy in health-care providers in Western countries: a narrative review. (3rd July 2022) - Verger, Pierre; Botelho-Nevers, Elisabeth; Garrison, Amanda; Gagnon, Dominique; Gagneur, Arnaud; Gagneux-Brunon, Amandine; Dubé, Eve
ABSTRACT: Introduction: Vaccine hesitancy (VH) is a leading cause of suboptimal vaccine uptake rates worldwide. The interaction between patients and health-care providers (HCPs) is the keystone in addressing VH. However, significant proportions of HCPs, including those who administer vaccines, are personally and professionally vaccine-hesitant. Areas covered: This narrative review sought to characterize the nature, extent, correlates, and consequences of VH among HCPs. We included 39 quantitative and qualitative studies conducted in Western countries, published since 2015, that assessed VH among HCPs in general, for several vaccines. Studies were reviewed using the WHO 3Cs model – (lack of) confidence, complacency, and (lack of) convenience. Expert opinion: Despite the lack of validated tools and substantial heterogeneity in the methods used to measure VH among HCPs, this review confirms its presence in this population, at frequencies that vary by country, profession type, setting, and level of medical education. Lack of knowledge and mistrust in health authorities/pharmaceutical industry/experts were among its principal drivers. Improving the content about vaccination in HCPs' training programs, facilitating access to reliable information for use during consultations, and developing and validating instruments to measure HCPs' VH and its determinants are key to addressing VH among HCPs.